Maturation of auditory brainstem responses in young children with congenital monaural atresia. (April 2017) - Stuermer, Konrad Johannes; Foerst, Astrid; Sandmann, Pascale; Fuerstenberg, Dirk; Lang-Roth, Ruth; Walger, Martin
Abstract: Objective: To date, the impact of conductive hearing loss on the auditory pathway at brainstem level has only been investigated in animal studies, which showed a species-specific delay of maturation. In this study, the functional maturation of auditory brainstem response (ABR) parameters in humans with unilateral atresia of the external auditory canal was investigated. Methods: 42 newborns and toddlers ranging in age from 13 days to 11 months were included. The click-evoked ABR interpeak latencies (IPL) of the atretic ears and the contralateral ears with normal hearing were evaluated. The children had no comorbidities and had never been fitted with any kind of hearing aid. The absolute latencies (AL) and IPL of a matched control group were compared to the contralateral normally hearing ears of the children with unilateral atresia. Results: The mean air-bone gap in the ears with atresia was 44 dB HL. Despite this partial acoustic deprivation, no significant difference between the IPLs of normal ears and ears with atresia could be detected. Both for AL and IPL, the differences between the normal ears and the control group were all within 1 standard deviation to the mean. Conclusion: The data showed that the monaural acoustic deprivation by a block of sound conduction does not produce any delay of functional maturation at brainstem level in this group of patients. With regard to the AL and IPL on brainstem level, no differences between the normal ears of children with unilateral atresia and children with bilateral normal hearing could be detected.